The importance of essential fatty acids and their ratios in aquafeeds to enhance salmonid production, welfare, and human health - Carr, Ian; Glencross, Brett; Santigosa, Ester (Frontiers in Animal Science, 2023)
Long chain polyunsaturated fatty acids (LC-PUFA), namely those from omega-3 (n-3) and omega-6 (n-6) families, are paramount for both fish and human nutrition. Some of these biomolecules cannot be synthesized de novo and must be acquired through the diet, being termed dietary essential fatty acids (EFA). Fish requirements for EFA have traditionally been met through the incorporation of fish oil (FO) in the formulation of aquafeeds. However, with limited supply of FO the aquaculture industry is searching for additional sustainable sources of LC-PUFA. This has significantly shifted the type of ingredients used in aquafeed formulation, namely vegetable oils (VO) deficient in long-chain omega-3, often resulting in imbalanced levels and ratios of fatty acid classes. Such imbalances can negatively affect fish performance and welfare, as well as the levels of health promoting omega-3 LC-PUFA present in fish fillets. Given the relevance that salmonid aquaculture plays in global fish production (principally Atlantic salmon, Salmo salar), as well as its growing role as a source of dietary health promoting omega-3 LC-PUFA for humans, the present review summarizes the scientific knowledge available to date on the dietary requirements for LC-PUFA by salmonids and humans. We discuss the implications of using imbalanced aquafeed formulations upon fish performance and welfare, as well as the subsequent consequences for human nutrition, along with current efforts to replace FO by alternative ingredients such as algal oil (AO) that can safeguard high-quality salmonid products for human consumption.